​​Internal Communication at Ringway, Milton Keynes​ - ​​Singh​, ​​Vartika​ (Cranfield University, 2025)
This thesis investigates internal communication practices at Ringway Milton Keynes, with a focus on enhancing employee engagement and organisational performance. Drawing on 15 semi-structured interviews across managers, office staff, and on-site operatives, the research applies Braun and Clarke’s (2006) six-phase thematic analysis to explore communication methods, trust, feedback practices, and opportunities for two-way dialogue. Findings highlight four key themes: fragmented communication channels, trust and accessibility, reliance on informal feedback over formal mechanisms, and suggestions for improvement. Results reveal that while employees trust their direct supervisors and value open, interpersonal exchanges, challenges persist with digital platforms in field settings, leadership visibility, and the utilisation of formal feedback systems. These insights confirm and extend existing theories such as Media Richness Theory (Daft & Lengel, 1986), Social Exchange Theory (Blau, 1964), and Psychological Safety (Edmondson, 1999), while also addressing gaps in literature around communication in dispersed, safety-critical industries. The study offers practical recommendations for Ringway, including simplified communication tools, enhanced leadership visibility, and structured feedback loops, alongside academic contributions on communication practices in hybrid and field-based workforces. By amplifying employee voices, this thesis bridges theory and practice, providing a roadmap for organisations seeking to build more inclusive and effective communication cultures.
​​Ringway, Milton Keynes​
Keywords: Internal communication; employee engagement; trust; two-way communication; Media Richness Theory; Social Exchange Theory; Psychological Safety; construction industry; hybrid workforce; thematic analysis; organisational communication